2015
DOI: 10.1093/ejcts/ezv426
|View full text |Cite
|
Sign up to set email alerts
|

State of the art: diagnostic tools and innovative therapies for treatment of advanced thymoma and thymic carcinoma

Abstract: In this review article, state-of-the-art diagnostic tools and innovative treatments of thymoma and thymic carcinoma (TC) are described with special respect to advanced tumour stages. Complete surgical resection (R0) remains the standard therapeutic approach for almost all a priori resectable mediastinal tumours as defined by preoperative standard computed tomography (CT). If lymphoma or germ-cell tumours are differential diagnostic considerations, biopsy may be indicated. Resection status is the most important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 73 publications
5
90
0
7
Order By: Relevance
“…As our unpublished study concerning thymus tumors revealed that, with increasing tumor size, patients' survival decreased significantly (detailed information is not shown). Besides, previous studies reported that complete resection significantly improved OS postoperatively (6,10,18,19), consistent with previous studies based on SEER (2,3). Information of resected marginal status could not be obtained from the SEER, posing an additional limitation in the present study as well.…”
supporting
confidence: 91%
“…As our unpublished study concerning thymus tumors revealed that, with increasing tumor size, patients' survival decreased significantly (detailed information is not shown). Besides, previous studies reported that complete resection significantly improved OS postoperatively (6,10,18,19), consistent with previous studies based on SEER (2,3). Information of resected marginal status could not be obtained from the SEER, posing an additional limitation in the present study as well.…”
supporting
confidence: 91%
“…On the basis of the morphology of epithelial cells and the lymphocyte to epithelial cell ratio, they are classified into five histological types, A, AB, B1, B2, and B3 [1]. The most widely used system for staging thymomas is the Masaoka–Koga staging system; according to this, thymomas are classified in stage I comprising encapsulated tumors, stages II and III showing direct local invasion, and stage IV showing metastatic spread [2]. Thymomas are associated with a wide variety of autoimmune diseases, and among these about 30%–40% of thymomas are associated with myasthenia gravis (MG), an autoimmune disease characterized by autoantibodies directed to different targets at the neuromuscular junction, such as acetylcholine receptor (AChR), muscle specific kinase (MuSK), and agrin-receptor low-density lipoprotein receptor related-protein 4 (LRP4) [3].…”
Section: Introductionmentioning
confidence: 99%
“…For giant soft tissue sarcoma, advanced thymic carcinoma, or malignant germ cell tumor, (especially an aggressive tumor with an abundant blood supply strongly suspected to be unresectable based on preoperative imaging manifestation), direct surgical treatment means a high possibility of conversion to debulking surgery or exploratory thoracotomy, increasing complication morbidity and poor prognosis. Therefore, neoadjuvant or even radical radiochemotherapy should be recommended for these selected patients prior to surgery …”
Section: Discussionmentioning
confidence: 99%